Analysis of Near-Surface Metal Contamination by Photoluminescence Measurements. (17th February 2018) - Polignano, M. L.; Galbiati, A.; Mica, I.; Magni, D.; Cseh, D.; Jay, F.; Basa, P.; Laurent, N.; Lajtos, I.; Molnar, G.; Dudas, L.; Roszol, L.; et al.
Abstract : In this work, molybdenum and tungsten-implanted wafers are analyzed by an innovative technique based upon photoluminescence measurements, with the aim to assess the ability of this technique to detect metal contamination in the near-surface region. Surface Photovoltage (SPV) measurements of carrier diffusion length are compared to the results of photoluminescence measurements. It is shown that molybdenum and tungsten contamination are easily detected by photoluminescence intensity measurements down to about 10 10 cm −2 contaminant dose. Vice versa, SPV has limited sensitivity to these elements (≥5·10 10 cm −2 ), because of their low diffusivity. Therefore, photoluminescence intensity measurement can be a valid alternative to conventional carrier diffusion length measurements for monitoring slow diffuser contamination.